1997
DOI: 10.1152/jappl.1997.82.4.1163
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of pulmonary perfusion and ventilation to heterogeneity in V˙a/Q˙measured by PET

Abstract: To estimate the contributions of the heterogeneity in regional perfusion (Q) and alveolar ventilation (V A) to that of ventilation-perfusion ratio (V A/Q), we have refined positron emission tomography (PET) techniques to image local distributions of Q and V A per unit of gas volume content (sQ and sV A, respectively) and V A/Q in dogs. sV A was assessed in two ways: 1) the washout of 13NN tracer after equilibration by rebreathing (sV A(i)), and 2) the ratio of an apneic image after a bolus intravenous infusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
93
2
4

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(130 citation statements)
references
References 32 publications
31
93
2
4
Order By: Relevance
“…These results can be explained by considering both the vertical distribution of the time constant and the interaction of noise level and absolute value of the time constant on the half CI/mean of the time constant. The time constants are longer in the nondependent regions than in the middle and dependent regions, which means that middle and dependent regions are better ventilated than the nondependent region, in agreement with many previous studies of regional ventilation distribution (17,25,38). According to the result of MC simulation performed by Simon et al (33), as the level of noise increases, the half CI/mean of the time constant increases to a greater degree for longer compared with shorter time Fig.…”
Section: Comparison Of 55 40 and 30% Xesupporting
confidence: 90%
See 2 more Smart Citations
“…These results can be explained by considering both the vertical distribution of the time constant and the interaction of noise level and absolute value of the time constant on the half CI/mean of the time constant. The time constants are longer in the nondependent regions than in the middle and dependent regions, which means that middle and dependent regions are better ventilated than the nondependent region, in agreement with many previous studies of regional ventilation distribution (17,25,38). According to the result of MC simulation performed by Simon et al (33), as the level of noise increases, the half CI/mean of the time constant increases to a greater degree for longer compared with shorter time Fig.…”
Section: Comparison Of 55 40 and 30% Xesupporting
confidence: 90%
“…Hoffman and colleague (14,15) found a significant vertical gradient of air content (3.3% air/cm at functional residual capacity) in the supine position, but a minimal gradient (Ϫ0.36% air/cm) in the prone position. Other studies found similar gradients of subpleural alveolar size (44), pleural pressure (41), and alveolar volume by PET (38) in the supine position, but no or minimal gradient in the prone position.…”
Section: Repeatability Of Xe-ct Methodsmentioning
confidence: 64%
See 1 more Smart Citation
“…PaO 2 in the supine position when ventilated without PEEP. This is in accordance with measurements of V/Q heterogeneity in dogs using PET (Treppo et al, 1997).…”
Section: Effects Of Peep and Positionsupporting
confidence: 91%
“…Ao melhorar a relação V/Q, houve também redução da fração de shunt (Qs/Qt). As áreas pouco aeradas na região dorsal são recrutadas com pouca ou nenhuma mudança na ventilação na região ventral do pulmão, provocando, assim, maior homogeneidade na relação V/Q (pela diminuição da proporção de áreas com reduzida V/Q) 11,[26][27][28][29][30] . A melhora da distribuição da relação V/Q na posição prona também pode ser comprovada em seres humanos, observando-se o recrutamento de áreas previamente atelectasiadas, mas sem doença 31 .…”
Section: Discussionunclassified